Analysis of Strengthening the Participation of Indigenous Peoples in Implementing the Qanun Concerning the Prevention and Management of CED in Pregnant Women in Gampong Cot Kuta, Suka Makmue District, Nagan Raya Regency - vita, Vita Ulvah; Fitriani; Farisni , Teungku Nih (Sean Institute, 2023)
The prevalence of CED risk based on data obtained from the Nagan Raya Health Office in Nagan Raya Regency itself in 2021 there were (4.6%) pregnant women with CED with 140 cases and sub-districts (13.2%) with 22 cases (Dinkes Nagan Raya, 2022), Therefore village and regional government policies are urgently needed in following up on CED problems, in Gampong Cot Kuta itself there is a Qanun that regulates the prevention and management of CED in pregnant women. So that it can be a reference in terms of implementing Qanun in Gampong Cot Kuta. The purpose of this research is to observe and describe the participation of indigenous peoples in implementing the Qanun on the prevention and management of CED in Gampong Cot Kuta. This research is descriptive in nature using qualitative research methods with data collection techniques used are observation and interviews. The results of this study found that all Tuha Peut in Gampong Cot Kuta have agreed to the draft Qanun that was implemented and provided support for this as evidenced by the number attendance who attended the FGD on 9 June 2022. However, some of Tuha Peut still do not have knowledge in carrying out their duties and roles in accordance with Qanun Gampong Cot Kuta No 5 of 2022. Based on the results of this analysis, it can be concluded that Tuha Peut has participated in implementing the Qanun although there are still some of Tuha Peut who still do not understand the contents of the Qanun and in terms of the implementation of CED prevention and control activities in Gampong Cot Kuta, although there are still some activities that have not been implemented.